ASEAN-5 Economic Growth Determination 2019-2023 - Willy Kurniawan; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
This study analyzes the influence of Foreign Direct Investment (FDI), population growth, government spending, and unemployment rates on economic growth in five ASEAN countries-Indonesia, Malaysia, Singapore, Thailand, and Vietnam for the 2019-2023 period. The method applied is quantitative descriptive analysis with a panel data regression model through the Fixed Effect Model (FEM) approach. The findings of the study describe that FDI has a positive and significant effect on economic growth, indicating the importance of foreign investment in encouraging production and technology transfer. On the other hand, population growth and unemployment have a negative and significant effect, reflecting demographic pressures and weak labor absorption. Meanwhile, government spending had no significant effect, indicating fiscal policy inefficiencies during the COVID-19 pandemic. Overall, the study emphasizes the role of FDI as a key driver of economic growth and the need for effective human resource management in the ASEAN region.